Antibodies Targeting Hsa and PadA Prevent Platelet Aggregation and Protect Rats against Experimental Endocarditis Induced by Streptococcus gordonii - Mancini, Stefano (Infect Immun, 2016)
Streptococcus gordonii and related species of oral viridans group streptococci (VGS) are common etiological agents of infective endocarditis (IE). We explored vaccination as a strategy to prevent VGS-IE, using a novel antigen-presenting system based on non-genetically modified Lactococcus lactis displaying vaccinogens on its surface. Hsa and PadA are surface-located S. gordonii proteins implicated in platelet adhesion and aggregation, which are key steps in the pathogenesis of IE. This function makes them ideal targets for vaccination against VGS-IE. In the present study, we report the use of nonliving L. lactis displaying at its surface the N-terminal region of Hsa or PadA by means of the cell wall binding domain of Lactobacillus casei A2 phage lysine LysA2 (Hsa-LysA2 and PadA-LysA2, respectively) and investigation of their ability to elicit antibodies in rats and to protect them from S. gordonii experimental IE. Immunized and control animals with catheter-induced sterile aortic valve vegetations were inoculated with 10(6) CFU of S. gordonii. The presence of IE was evaluated 24 h later. Immunization of rats with L. lactis Hsa-LysA2, L. lactis PadA-LysA2, or both protected 6/11 (55%), 6/11 (55%), and 11/12 (91%) animals, respectively, from S. gordonii IE (P < 0.05 versus controls). Protection correlated with the induction of high levels of functional antibodies against both Hsa and PadA that delayed or totally inhibited platelet aggregation by S. gordonii. These results support the value of L. lactis as a system for antigen delivery and of Hsa and PadA as promising candidates for a vaccine against VGS-IE.